Effects of Back Massage and Music Relaxation on Blood Pressure among Patients with Hypertension: A Literature Review - Lino Aparicio Pires Gusmão; Indah Sri Wahyuningsih; Dwi Heppy Rochmawati; Erna Melastuti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a leading contributor to cardiovascular morbidity and mortality. Non-pharmacological strategies such as back massage and music relaxation have been proposed to attenuate sympathetic activation and stabilize blood pressure. Grounded in relaxation theory and stress physiology, this review synthesizes current evidence on the effectiveness of these interventions in patients with hypertension. A systematic review was conducted in accordance with PRISMA guidelines across national and international databases (2020–2025). The research question was structured using the PICO framework. Quasi-experimental and randomized controlled trials involving hypertensive patients and reporting pre–post or between-group changes in blood pressure were eligible. Of 312 records identified, 97 duplicates were removed. After title–abstract screening of 215 records and full-text assessment of 69 articles, 15 studies met the inclusion criteria and were narratively synthesized. Most studies demonstrated statistically significant reductions in systolic and diastolic blood pressure following back massage, music therapy, or combined relaxation approaches. However, notable heterogeneity was observed in intervention protocols, duration, comparators, and control for confounding factors. Back massage and music relaxation appear to be safe, complementary interventions with promising potential to reduce blood pressure among individuals with hypertension. Nonetheless, rigorously designed randomized controlled trials with standardized protocols and longer follow-up are warranted to strengthen the evidence base.